Thomas Clarkson's Heterodox Anglican Christianity and Anti-Slavery - Page, Anthony 1969- (2024)
This article argues that Thomas Clarkson (1760-1846), the founder of the British campaign to abolish the slave trade, was a heterodox Anglican. Suspected of ‘Unitarian opinions’ in his youth, his religious writings in old age, including neglected notes on his copy of the New Testament, display a deep commitment to critical study of the Bible and a broadly Arian view of Christ. Knowing that Clarkson was a life-long but heterodox member of the Church of England challenges the conventional focus on Quakers and Evangelicals in the study of religion and abolitionism.